Magnetic impurity in topological nodal loop semimetals. (4th October 2018) - Deng, Ying-Hua; Lü, Hai-Feng; Ke, Sha-Sha; Guo, Yong; Zhang, Huai-Wu
Abstract: We investigate the Kondo effect of a spin-1/2 magnetic impurity in a topological nodal loop semimetal, in which band touchings form a nodal loop. The Fermi surface of a nodal loop semimetal is a torus or a drum-like structure, which is determined by chemical potential. When the chemical potential μ lies at the nodal loop ( ), the magnetic impurity and the conduction electrons form bound states only if their coupling exceeds a critical value. As the chemical potential is tuned away from the nodal loop, the Fermi surface becomes a torus or drum-like structure and the impurity and the host material always favor a bound state due to the finite density of state. Due to the anisotropic dispersion relationship in the energy band, the spatial spin–spin correlations ( ) are of power-law decay with the decay rates proportional to and in different directions, respectively. The product and oscillates in coordinate space and the period is enhanced gradually as the Fermi surface evolves from a torus surface into a drum-like structure.